Anglican enlightenment : orientalism, religion and politics in England and its empire, 1648–1715 by William J. Bulman (Review) - Galbraith, Jeffrey (2020)
The Enlightenment, in its traditional, boiled-down form, describes the European intellectual movement that rejected older forms of religion and knowledge in pursuit of rationalism and science. Philosophical in nature, anticlerical in impulse, the Enlightenment was the product of emancipating ideas, the embrace of which led to the production of mature, autonomous individuals. This traditional account of the Enlightenment, viewed as heralding the dawn of secular liberalism, has met resistance from scholars who argue that traditional knowledge and belief frequently proved compatible with new ideas. Recent scholarship has gone a step further in laying down its challenge to the standard view. Current work focuses on the role of media in the period, attending foremost to the articulation and dissemination of ideas rather than to the ideas themselves. Such an approach yields a thicker, more insightful description of the changes occurring in late-seventeenth-century England. Historian William J. Bulman’s examination of the Anglican clergyman Lancelot Addison joins this growing body of scholarship. In Anglican Enlightenment: Orientalism, Religion and Politics in England and Its Empire, 1648–1715, Bulman argues that the clergyman’s life and writings reveal a phase of enlightenment that preceded the latitudinarian, rationalist Anglicanism of the eighteenth century.